Biphase hypoeutectic copper-zirconium alloy and supergravity preparation method thereof

Through supergravity solidification technology, the microstructure of copper-zirconium alloy is regulated, and the problem of insufficient density and mechanical properties of copper-zirconium alloy materials is solved, achieving efficient short-process preparation and performance improvement.

CN119307773APending Publication Date: 2025-01-14ZHEJIANG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411349623.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The copper-zirconium alloy material has problems such as poor density, coarse grain structure, high impurity content of ingots and unsatisfactory mechanical properties. The existing process is complex and costly.

Method used

The supergravity preparation method of biphasic subeutectic copper-zirconium alloy is used to regulate the supergravity field strength to form through the mixed vacuum smelting and casting of electrolytic copper and metal zirconium, combined with wire cutting, mechanical grinding, ultrasonic cleaning and supergravity solidification technology. Densified, high-performance copper-zirconium alloy.

Benefits of technology

The yield strength and tensile strength of cast copper-zirconium alloy are significantly improved, while maintaining good elongation, achieving efficient and short-process preparation, simplifying the process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307773A_ABST
    Figure CN119307773A_ABST
Patent Text Reader

Abstract

The invention discloses a biphase hypoeutectic copper-zirconium alloy and a supergravity preparation method thereof. The method comprises the steps that electrolytic copper and metal zirconium are put into a smelting furnace to be subjected to vacuum smelting and pouring, and a cast ingot is obtained; the cast ingot is sequentially subjected to cutting, grinding, ultrasonic cleaning and drying, and a copper-zirconium raw material is obtained; processing the copper-zirconium raw material into a plurality of cast ingots, and placing the cast ingots in a crucible; the whole crucible is placed in a muffle furnace for vacuum heating and heat preservation; and after heat preservation is finished, the crucible is placed in a hanging cup of a centrifugal machine, the centrifugal machine is started immediately to enable the cast ingot to rotate, and after the crucible is completely cooled to the room temperature, the block cast ingot is taken out. According to the method, the super-gravity field is applied on the basis of vacuum melting and constant gravity solidification of the Cu-Zr alloy, the morphology and distribution characteristics of a primary phase and a eutectic structure are regulated and controlled only by changing the intensity of the super-gravity field, the yield strength and the tensile strength of the as-cast copper alloy are efficiently and conveniently optimized, and good ductility is kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper alloys, and in particular relates to an ultra-gravity preparation method of a two-phase hypoeutectic copper-zirconium alloy. Background Art

[0002] Solidification is one of the most basic molding technologies for preparing materials. Solidification technology is based on solidification theory. It is a technology that obtains the desired material performance and the casting without solidification defects by controlling the solidification process. Introducing various physical fields into the metal solidification process is a hot topic in the current solidification research field. As a result, new solidification research fields such as electromagnetic field solidification, ultra-gravity solidification, and ultrasonic solidification have emerged. Ultra-gravity solidification changes the heat and mass transfer process through forced convection, thereby affecting the nucleation rate, the temperature gradient at the front of the solidification interface, and the solute field. By optimizing the process parameters such as centrifugal ultra-gravity, solidification rate, and temperature gradient, the controllable preparation of high-performance materials can be achieved.

[0003] Due to its excellent mechanical properties, copper-zirconium alloy has broad application prospects in high-tech fields such as aviation, aerospace, high-speed rail, and high-voltage power transmission. In conventional copper-zirconium alloy castings, the grains are coarse, the eutectic phase is small and easily precipitated at the grain boundary, resulting in the eutectic phase not contributing significantly to the alloy strength. Therefore, in order to improve the strength of copper-zirconium alloy, on the one hand, microalloying is performed, such as the use of Ti in patent CN104718302B, Co and B in patent CN103380221B, Si in patent CN105452502B, Ni, Si, Ag and rare earth elements in patent CN105088010B, and Mg, Si and rare earth elements in CN111411256A; on the other hand, a long process preparation process is adopted, such as patent CN117418135A provides a preparation method for copper-zirconium alloy rings, the preparation process includes smelting, casting, hot forging and solution treatment, one cold forging and one heat treatment, two cold forging and two heat treatments. Although the above processes have improved the mechanical properties of copper-zirconium alloys to varying degrees, the added microalloying elements are mostly active elements, which are easily burned during the casting process. In addition, the content is relatively small, making it difficult to accurately control. The long process is complex, highly dependent on equipment, and has high product preparation costs. The current cast copper-zirconium alloy materials still have problems such as poor density, coarse grain structure, high impurity content in ingots, and unsatisfactory mechanical properties. Summary of the invention

[0004] In order to solve the problems existing in the background technology, the purpose of the present invention is to provide a supergravity preparation method of a two-phase hypoeutectic copper-zirconium alloy, in view of the fact that cast copper-zirconium alloy materials still have problems such as poor density, coarse grain structure, high impurity content in the ingot and unsatisfactory mechanical properties.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] 1. A two-phase hypoeutectic copper-zirconium alloy:

[0007] The two-phase hypoeutectic copper-zirconium alloy is mainly prepared by mixing electrolytic copper and metal zirconium; in the two-phase hypoeutectic copper-zirconium alloy, the mass percentage content of the metal zirconium is 4% to 6%, and the mass percentage content of the electrolytic copper is 94% to 96%.

[0008] In the dual-phase hypoeutectic copper-zirconium alloy, the mass percentage content of metal zirconium is 5%.

[0009] 2. A method for preparing the dual-phase hypoeutectic copper-zirconium alloy, comprising the following steps:

[0010] Step S1, first, electrolytic copper and metal zirconium are placed in a smelting furnace for vacuum smelting and pouring to obtain a casting ingot;

[0011] Step S2, sequentially subjecting the cast ingot obtained in step S1 to wire cutting, mechanical grinding, ultrasonic cleaning and constant temperature drying to obtain a copper-zirconium raw material, wherein the copper-zirconium raw material is used to prepare a copper-zirconium alloy under high gravity;

[0012] Step S3: The copper-zirconium raw material of step S2 is then processed by wire cutting into a volume of approximately 1 cm 3 Several block ingots are cast, and all the block ingots are placed inside the crucible;

[0013] Step S4, then installing a round cover on the top of the crucible to prevent heat loss and element volatilization during the ultra-gravity solidification process;

[0014] Step S5, placing the crucible with the round cover in a muffle furnace for vacuum heating and heat preservation;

[0015] Step S6, symmetrically fixing two hanging cups on the horizontal rotor of the centrifuge, connecting the horizontal rotor with an electric slip ring, and equipping the centrifuge with a speed sensor, which is used to measure the speed of the centrifuge;

[0016] Step S7, adjusting the dynamic rotation balance of the horizontal rotor under the hanging cup no-load condition to control the dynamic unbalance of the centrifuge;

[0017] Step S8, ultra-gravity solidification: after the heat preservation is completed, the vacuum-heated crucible is taken out from the muffle furnace and quickly placed in one of the hanging cups of the centrifuge, a counterweight for balancing the centrifuge is installed in the other hanging cup, and then the centrifuge is started, and the speed of the horizontal rotor is adjusted so that the horizontal rotor carrying the crucible rotates at a high speed;

[0018] Step S9: During the rotation of the horizontal rotor, after the crucible is completely cooled to room temperature, the horizontal rotor is controlled to stop rotating, and the bulk ingot is taken out to obtain a duplex hypoeutectic copper-zirconium alloy sample.

[0019] The solidified sample (two-phase hypoeutectic copper-zirconium alloy) obtained in step S9 was cut in half along the axial midline, a sheet sample was cut along the bottom of the solidified sample, and a scanning electron microscope analysis was performed, and a tensile sample was cut along the bottom and ground to 2000# with diamond sandpaper to remove surface defects. The yield strength, tensile strength and elongation of the copper-zirconium alloy prepared under different ultra-gravity conditions were tested using a universal testing machine. To ensure the reliability of the experimental data, each group of samples was tested at least 3 times.

[0020] In the step S1, the mass ratio of electrolytic copper to metal zirconium is 4:96 to 6:94.

[0021] In the step S2, the ultrasonic cleaning agent used to ultrasonically clean the cast ingot is anhydrous ethanol.

[0022] The ultrasonic cleaning is preferably performed in an ultrasonic cleaning machine. The present invention has no particular limitation on the type of the ultrasonic cleaning machine, and any equipment well known to those skilled in the art can be used.

[0023] The vacuum heating conditions of the crucible in the muffle furnace in step S5 are as follows: the vacuum degree is greater than 10 -3 Pa, the crucible is heated with the muffle furnace to a temperature not lower than 1250°C, and the holding time is not less than 45 min.

[0024] In step S7, the dynamic unbalance of the centrifuge is less than 2 g·mm.

[0025] In the step S8, the rotation speed of the horizontal rotor is adjusted so that the rotation speed of the crucible is greater than 1000 r / min.

[0026] In the step S8, a low thermal conductivity insulation sleeve is filled between the vacuum heated crucible and the inner wall of the hanging cup to reduce heat loss along the side wall of the crucible, and the thermal conductivity of the insulation sleeve is lower than 0.2 W / (m·K).

[0027] The crucible containing the raw materials preferably has an inner diameter of 20 mm, a wall thickness of 4 mm, and a height of 122 mm. The compact dome preferably has a diameter of 19.5 mm and a thickness of 10 mm. The horizontal rotor preferably rotates for 10 minutes.

[0028] The vacuum heating conditions of the crucible in the muffle furnace in step S5 are as follows: the crucible is heated to 1300° C. with the muffle furnace, and the heat preservation time is 60 minutes.

[0029] During the experiment, the centrifuge speed was adjusted to change the centrifugal acceleration required for supergravity solidification according to the experimental needs. For example, when the rotation speed of the horizontal rotor was set to 0 r / min, the supergravity at the bottom of the crucible was 1G (G = 9.8 m / s 2 ), at this time, a sample solidified under normal gravity (1G) is obtained; when the rotation speed of the horizontal rotor is set to 1687r / min, the supergravity corresponding to the bottom of the crucible is 500G (G=9.8m / s 2 ); when the rotation speed of the horizontal rotor is set to 2386r / min, the corresponding excess gravity at the bottom of the crucible is 1000G; when the rotation speed of the horizontal rotor is set to 2922r / min, the corresponding excess gravity at the bottom of the crucible is 1500G.

[0030] The present invention intends to use a high-speed rotating centrifuge to form a centrifugal supergravity field in the melting furnace, and use the buoyancy convection effect generated by the supergravity to strengthen the density difference, and control the nucleation growth behavior and solidification process through factors such as temperature, cooling rate, and supergravity parameters. Under the premise of not undergoing a series of complicated processes such as thermal-mechanical treatment, the supergravity preparation of the two-phase hypoeutectic copper-zirconium alloy is achieved. Only by regulating the intensity of the supergravity field, the efficient and short-process preparation of the densified and high-performance copper-zirconium alloy is achieved. Therefore, by applying a supergravity field to control the microstructure of the cast copper alloy and optimize the comprehensive mechanical properties of the cast copper alloy, the alloy preparation cycle is significantly shortened, which has strong practical significance and application prospects.

[0031] The present invention provides a preparation method of a two-phase hypoeutectic copper-zirconium alloy, the chemical composition of which includes, by mass percentage, 5% Zr and the balance Cu. Under 1G solidification conditions, the microstructure of the hypoeutectic copper-zirconium alloy is mainly composed of neatly arranged dendritic phases, and the secondary dendrite arms grow perpendicular to the dendrite trunks. The narrow and long eutectic structure is distributed in the gap position of the natal phase, and the distribution is uneven. Under supergravity solidification conditions, as the intensity of the supergravity field gradually increases, the directionally grown dendrites are continuously broken and refined, and the secondary dendrite arms gradually separate from the dendrite trunks to form fine equiaxed primary phases. When the supergravity field intensity is 1500G, the fine equiaxed primary phase and the continuous eutectic structure are evenly distributed, forming a dispersed network two-phase structure.

[0032] The present invention adopts the high-gravity solidification technology to regulate the nucleation growth behavior and the solidification process by means of factors such as temperature, cooling rate, and high-gravity parameters. Without undergoing a series of complicated processes such as thermal-mechanical treatments, the high-gravity field intensity is regulated to achieve the high-gravity preparation of the two-phase hypoeutectic copper-zirconium alloy in the melt solidification stage, thereby effectively improving the yield strength and tensile strength of the cast hypoeutectic Cu-5Zr alloy while maintaining good ductility, thereby achieving the short-process preparation of the densified and high-performance copper-zirconium alloy.

[0033] The beneficial effects of the present invention are:

[0034] 1. The present invention applies a hypergravity field on the basis of normal gravity solidification of Cu-Zr alloy. By only changing the intensity of the hypergravity field, the morphology and distribution characteristics of the primary phase and eutectic structure are regulated, thereby significantly optimizing the yield strength and tensile strength of the cast copper alloy and maintaining good elongation.

[0035] 2. The high-efficiency short-process ultra-gravity solidification technology provided by the present invention has a short preparation process cycle and is simple and convenient to operate. The oriented dendrite structure obtained under normal gravity solidification conditions is gradually transformed into a diffuse network structure composed of fine equiaxed primary phase and uniform eutectic structure, which significantly improves the yield strength and tensile strength of the cast copper-zirconium alloy while maintaining good elongation. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the microstructure diagram of the hypoeutectic copper-zirconium alloy prepared under normal gravity (1G) in Comparative Example 1;

[0037] Figure 2 This is the microstructure of the hypoeutectic Cu-5Zr alloy prepared by ultra-gravity (500G) in Example 2;

[0038] Figure 3 This is the microstructure of the hypoeutectic Cu-5Zr alloy prepared by ultra-gravity (1000G) in Example 3;

[0039] Figure 4 This is the microstructure of the hypoeutectic Cu-5Zr alloy prepared by ultra-gravity (1500G) in Example 4;

[0040] Figure 5 The engineering stress-engineering strain curves of the hypoeutectic Cu-5Zr alloys prepared under ultra-gravity in Examples 1-3 and under normal gravity in Comparative Example 1. DETAILED DESCRIPTION

[0041] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Example 1

[0043] The 500G ultra-gravity preparation method of the dual-phase hypoeutectic copper-zirconium alloy Cu-Zr alloy comprises the following steps:

[0044] (1) First, electrolytic copper and metal zirconium are placed in a smelting furnace for vacuum smelting and pouring to obtain a cast ingot, wherein the mass percentage of the metal zirconium is 5%;

[0045] (2) The cast ingot obtained in step S1 is subjected to wire cutting, mechanical grinding, ultrasonic cleaning with ethanol in an ultrasonic cleaning machine, and then constant temperature drying in a blast drying oven to obtain a copper-zirconium raw material for preparing a copper-zirconium alloy under ultra-gravity. The copper-zirconium raw material is then processed by wire cutting into a volume of approximately 1 cm 3 Several block ingots are cast, and all the block ingots are placed in a crucible with an inner diameter of 20 mm;

[0046] (3) A 20 mm diameter round cover was then installed on the top of the crucible to prevent heat loss and Zr volatilization during the ultra-gravity solidification process. Subsequently, the crucible containing the ingot was placed in a muffle furnace for vacuum heating. The crucible was heated to 1300 °C with the furnace and the vacuum degree was 10 -3 Pa, and keep warm for 60min;

[0047] (4) Two hanging cups are symmetrically fixed on the horizontal rotor of the centrifuge, and the horizontal rotor is connected to the electric slip ring, and a speed sensor is installed on the centrifuge; when the hanging cups are unloaded, the dynamic rotation balance of the horizontal rotor is adjusted to ensure that the dynamic unbalance of the centrifuge is less than 2g·mm;

[0048] (5) After the insulation stage is completed, the crucible containing the alloy ingot is quickly placed in the hanging cup of the centrifuge turntable, and a sleeve of insulation material with low thermal conductivity is placed in the gap between the hanging cup and the crucible to prevent heat dissipation along the side wall of the crucible;

[0049] (6) Under the condition of supergravity solidification, the rotating speed of the centrifuge equipped with a high-speed electric slip ring is set to 1687 r / min, and the supergravity field strength at the bottom of the crucible corresponds to 500 G. After the alloy melt in the crucible is completely cooled to room temperature, the supergravity (500 G) alloy ingot is taken out to prepare the duplex hypoeutectic copper-zirconium alloy sample.

[0050] (7) The alloy ingot sample is cut flat along the diameter direction. The sample is cut from the bottom of the ingot and analyzed by scanning electron microscopy.

[0051] Example 2

[0052] The 1000G ultra-gravity preparation method of the dual-phase hypoeutectic copper-zirconium alloy Cu-Zr alloy comprises the following steps:

[0053] (1) First, electrolytic copper and metal zirconium are placed in a smelting furnace for vacuum smelting and pouring to obtain a cast ingot, wherein the mass percentage of the metal zirconium is 5%;

[0054] (2) The cast ingot obtained in step S1 is subjected to wire cutting, mechanical grinding, ultrasonic cleaning with ethanol in an ultrasonic cleaning machine, and then constant temperature drying in a blast drying oven to obtain a copper-zirconium raw material for preparing a copper-zirconium alloy under ultra-gravity. The copper-zirconium raw material is then processed by wire cutting into a volume of approximately 1 cm 3 Several block ingots are cast, and all the block ingots are placed in a crucible with an inner diameter of 20 mm;

[0055] (3) A 20 mm diameter round cover was then installed on the top of the crucible to prevent heat loss and Zr volatilization during the ultra-gravity solidification process. Subsequently, the crucible containing the ingot was placed in a muffle furnace for vacuum heating. The crucible was heated to 1300 °C with the furnace and the vacuum degree was 10 -3 Pa, and keep warm for 60min;

[0056] (4) Two hanging cups are symmetrically fixed on the horizontal rotor of the centrifuge, and the horizontal rotor is connected to the electric slip ring, and a speed sensor is installed on the centrifuge; when the hanging cups are unloaded, the dynamic rotation balance of the horizontal rotor is adjusted to ensure that the dynamic unbalance of the centrifuge is less than 2g·mm;

[0057] (5) After the insulation stage is completed, the crucible containing the alloy ingot is quickly placed in the hanging cup of the centrifuge turntable, and a sleeve of insulation material with low thermal conductivity is placed in the gap between the hanging cup and the crucible to prevent heat dissipation along the side wall of the crucible;

[0058] (6) Under the condition of supergravity solidification, the rotating speed of the centrifuge equipped with a high-speed electric slip ring is set to 2386 r / min, and the supergravity field strength at the bottom of the crucible corresponds to 1000 G. After the alloy melt in the crucible is completely cooled to room temperature, the supergravity (1000 G) alloy ingot is taken out to prepare the duplex hypoeutectic copper-zirconium alloy sample.

[0059] (7) The alloy ingot sample is cut flat along the diameter direction. The sample is cut from the bottom of the ingot and analyzed by scanning electron microscopy.

[0060] Example 3

[0061] The 1500G ultra-gravity preparation method of the dual-phase hypoeutectic copper-zirconium alloy Cu-Zr alloy comprises the following steps:

[0062] (1) First, electrolytic copper and metal zirconium are placed in a smelting furnace for vacuum smelting and pouring to obtain a cast ingot, wherein the mass percentage of the metal zirconium is 5%;

[0063] (2) The cast ingot obtained in step S1 is subjected to wire cutting, mechanical grinding, ultrasonic cleaning with ethanol in an ultrasonic cleaning machine, and then constant temperature drying in a blast drying oven to obtain a copper-zirconium raw material for preparing a copper-zirconium alloy under ultra-gravity. The copper-zirconium raw material is then processed by wire cutting into a volume of approximately 1 cm3 Several block ingots are cast, and all the block ingots are placed in a crucible with an inner diameter of 20 mm;

[0064] (3) A 20 mm diameter round cover was then installed on the top of the crucible to prevent heat loss and Zr volatilization during the ultra-gravity solidification process. Subsequently, the crucible containing the ingot was placed in a muffle furnace for vacuum heating. The crucible was heated to 1300 °C with the furnace and the vacuum degree was 10 -3 Pa, and keep warm for 60min;

[0065] (4) Two hanging cups are symmetrically fixed on the horizontal rotor of the centrifuge, and the horizontal rotor is connected to the electric slip ring, and a speed sensor is installed on the centrifuge; when the hanging cups are unloaded, the dynamic rotation balance of the horizontal rotor is adjusted to ensure that the dynamic unbalance of the centrifuge is less than 2g·mm;

[0066] (5) After the insulation stage is completed, the crucible containing the alloy ingot is quickly placed in the hanging cup of the centrifuge turntable, and a sleeve of insulation material with low thermal conductivity is placed in the gap between the hanging cup and the crucible to prevent heat dissipation along the side wall of the crucible;

[0067] (6) Under the condition of supergravity solidification, the rotating speed of the centrifuge equipped with a high-speed electric slip ring is set to 2922 r / min, and the supergravity field strength corresponding to the bottom of the crucible is 1500 G. After the alloy melt in the crucible is completely cooled to room temperature, the supergravity (1500 G) alloy ingot is taken out to prepare the duplex hypoeutectic copper-zirconium alloy sample.

[0068] (7) The alloy ingot sample is cut flat along the diameter direction. The sample is cut from the bottom of the ingot and analyzed by scanning electron microscopy.

[0069] Comparative Example 1

[0070] The preparation method of the dual-phase hypoeutectic copper-zirconium alloy comprises the following steps:

[0071] (1) The purchased hypoeutectic Cu-Zr alloy was subjected to wire cutting, mechanical grinding, ultrasonic cleaning with ethanol in an ultrasonic cleaning machine, and then constant temperature drying in a blast drying oven to obtain the raw material, and then the raw material was processed by wire cutting into a volume of approximately 1 cm 3 Several block ingots are cast, and all the block ingots are placed in a crucible with an inner diameter of 20 mm;

[0072] (2) A 20 mm diameter round cover was then installed on the top of the crucible to prevent heat loss and Zr volatilization during the ultra-gravity solidification process. The crucible containing the ingot was then placed in a muffle furnace for vacuum heating. The crucible was heated to 1300°C and the vacuum degree was 10 -3 Pa, and keep warm for 60min;

[0073] (3) Two hanging cups are symmetrically fixed on the horizontal rotor of the centrifuge, and the horizontal rotor is connected to the electric slip ring, and a speed sensor is installed on the centrifuge; when the hanging cups are unloaded, the dynamic rotation balance of the horizontal rotor is adjusted to ensure that the dynamic unbalance of the centrifuge is less than 2g·mm;

[0074] (4) After the insulation stage is completed, the crucible containing the alloy ingot is quickly placed in the hanging cup of the centrifuge turntable, and a sleeve of insulation material with low thermal conductivity is placed in the gap between the hanging cup and the crucible to prevent heat dissipation along the side wall of the crucible;

[0075] (5) Under normal gravity conditions, the crucible is stationary inside the hanging cup and the centrifuge is stationary. After the alloy melt in the crucible is completely cooled to room temperature, the alloy ingot is taken out and prepared under normal gravity.

[0076] (6) The alloy ingot sample is cut flat along the diameter direction. The sample is cut from the bottom of the ingot and analyzed by scanning electron microscopy.

[0077] Tensile sheets were cut from the longitudinal bottom of the hypoeutectic copper-zirconium alloys prepared under ultra-gravity in Examples 1-3 and the hypoeutectic copper-zirconium alloys prepared under normal gravity in Comparative Example 1, and tensile tests were carried out at room temperature. The tensile strain rate was 10 -3 / s, equipped with a video extensometer to calculate strain in real time, the engineering stress-strain curve results are as follows Figure 5 shown.

[0078] Figure 1 This is the microstructure of the hypoeutectic Cu-5Zr alloy prepared under normal gravity (1G) in Comparative Example 1. Figure 1 It can be seen that under normal gravity (1G), the microstructure of the alloy is mainly a well-developed primary dendrite phase (α-Cu) arranged regularly, with abundant secondary dendrite arms and dendrite trunks perpendicular to each other, both of which are dark phases. The light-colored eutectic structure is composed of Cu5Zr intermetallic compounds and Cu phases arranged alternately. The eutectic structure is thin-lamellar as a whole, discontinuously distributed, and embedded in the gap between the primary dendrite trunk and the secondary dendrite arm. Even if the insulation effect of the insulation material sleeve is good, there is still a certain temperature gradient along the side wall of the crucible. The superimposed temperature gradient in the vertical direction causes the dendrite growth direction to be tilted at a certain angle relative to the vertical direction. In general, the hypoeutectic Cu-5Zr alloy obtained a regularly arranged directional solidification primary dendrite phase under normal gravity (1G) solidification conditions, and the thin-lamellar eutectic structure is discontinuously distributed in the gap between the dendrite trunk and the dendrite arm.

[0079] Figure 2 This is the microstructure diagram of the hypoeutectic Cu-5Zr alloy prepared by ultragravity (500G) in Example 1.

[0080] from Figure 2 It can be seen that when the horizontal rotor rotation speed is 1687r / min and the supergravity field strength is 500G, the microstructure of the 500G supergravity solidified Cu-5Zr alloy has changed significantly compared with the normal gravity condition. Compared with the 1G sample, the complete and continuous primary dendrites in the microstructure of the 500G sample have been fragmented to a certain extent, but the dendrites with a length of more than 1mm are still retained, and the width of the dendrites is also reduced. The growth direction of the dendrites is relatively scattered, and the growth direction of the dendrites is relatively large. Figure 1 The orientation of the dendrite phase has been significantly tilted. At the same time, some secondary dendrite arms have fallen off and separated from the dendrite trunk, evolving into fine and nearly equiaxed spherical primary phases. Compared with the normal gravity conditions, the thickness of the eutectic structure has increased significantly. Part of the continuous eutectic structure and the refined spherical primary phase are locally arranged into a grid-like morphology, and a small amount of black casting pore defects are observed in the enlarged microstructure diagram.

[0081] Figure 3 This is the microstructure diagram of the hypoeutectic Cu-5Zr alloy prepared by ultragravity (1000G) in Example 2.

[0082] from Figure 3 It can be seen that when the horizontal rotor rotation speed is 2386r / min, the supergravity field strength is further increased to 1000G, and the length of the residual primary dendrite is further reduced. The fragmentation degree of most secondary dendrite arms is also significantly increased, and the continuous eutectic structure and refined primary phase are more evenly distributed. There are almost no casting pore defects in the enlarged microstructure diagram, which indicates that when the supergravity field strength reaches 1000G, the density of the hypoeutectic Cu-5Zr cast alloy is significantly improved.

[0083] Figure 4 This is the microstructure diagram of the hypoeutectic Cu-5Zr alloy prepared by ultra-gravity (1500G) in Example 3.

[0084] from Figure 4 It can be seen that when the horizontal rotor rotation speed is 2922r / min and the supergravity intensity reaches 1500G, the coarse primary dendrite phase is almost not observed in the hypoeutectic Cu-5Zr alloy structure, and the initial dendrite phase has been completely broken into a fine equiaxed phase. The eutectic structure is evenly distributed in the gap position of the approximately equiaxed spherical phase, forming a diffuse network structure composed of the primary Cu phase and the eutectic structure. Compared with the normal gravity solidification condition, the primary dendrite phase is gradually broken and transformed from regularly arranged directional dendrites to fine equiaxed spheres, the volume fraction of the eutectic structure increases, and the distribution is more uniform.

[0085] The yield strength, tensile strength and elongation of the normal gravity Cu-5Zr alloy prepared in Comparative Example 1 and the high gravity Cu-5Zr alloy prepared in Examples 1-3 were compared at room temperature. The results are shown in Table 1.

[0086] Table 1 Yield strength, tensile strength and elongation of hypoeutectic Cu-5Zr alloy prepared by ultra-gravity solidification

[0087]

[0088] As can be seen from Table 1, the strength of the hypoeutectic Cu-5Zr supergravity solidified samples obtained in Examples 1-3 is steadily improved. The greater the intensity of the applied supergravity field, the higher the yield strength and tensile strength of the alloy. When the supergravity field intensity is 1500G, the yield strength and tensile strength of the hypoeutectic Cu-5Zr alloy are increased by 131.3MPa and 146MPa respectively compared with the normal gravity solidification conditions, while maintaining a high elongation (12.4%).

[0089] From the above examples and comparative examples, it can be seen that the yield strength and tensile strength of the hypoeutectic copper-zirconium alloy prepared by 1500G ultra-gravity provided by the present invention are significantly improved, and have good elongation. The microstructure of the copper alloy is regulated by applying an ultra-gravity field, and the mechanical properties of the cast alloy are significantly optimized.

[0090] The present invention applies a hypergravity field of different strengths on the basis of solidification of Cu-5Zr alloy under normal gravity conditions, effectively breaking and refining the primary dendrite phase and secondary dendrite arms into fine equiaxed primary phases, significantly increasing the volume fraction of the eutectic structure, and presenting a more uniform distribution feature. The present invention uses hypergravity solidification technology to regulate the nucleation growth behavior and solidification process through factors such as temperature, cooling rate, and hypergravity parameters. Without a series of complicated processes such as thermal-mechanical treatment, the present invention realizes the hypergravity preparation of a two-phase hypoeutectic copper-zirconium alloy, effectively improving the yield strength and tensile strength of the cast hypoeutectic Cu-5Zr alloy, while maintaining good ductility.

[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A two-phase hypoeutectic copper-zirconium alloy, characterized in that: The two-phase hypoeutectic copper-zirconium alloy is mainly prepared by mixing electrolytic copper and metal zirconium; in the two-phase hypoeutectic copper-zirconium alloy, the mass percentage content of the metal zirconium is 4% to 6%, and the mass percentage content of the electrolytic copper is 94% to 96%.

2. A two-phase hypoeutectic copper-zirconium alloy according to claim 1, characterized in that: In the dual-phase hypoeutectic copper-zirconium alloy, the mass percentage content of metal zirconium is 5%.

3. A method for preparing a dual-phase hypoeutectic copper-zirconium alloy as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: Step S1, first, electrolytic copper and metal zirconium are placed in a smelting furnace for vacuum smelting and pouring to obtain a casting ingot; Step S2, sequentially subjecting the cast ingot obtained in step S1 to wire cutting, mechanical grinding, ultrasonic cleaning and constant temperature drying to obtain a copper-zirconium raw material, wherein the copper-zirconium raw material is used to prepare a copper-zirconium alloy under high gravity; Step S3, then the copper-zirconium raw material of step S2 is processed into a plurality of block ingots by wire cutting, and all the block ingots are placed in a crucible; Step S4, then installing a round cover on the top of the crucible with the block ingot placed therein, the round cover is used to prevent heat loss and element volatilization during the ultra-gravity solidification process; Step S5, placing the crucible with the round cover in a muffle furnace for vacuum heating and heat preservation; Step S6, symmetrically fixing two hanging cups on the horizontal rotor of the centrifuge, connecting the horizontal rotor with an electric slip ring, and equipping the centrifuge with a speed sensor; Step S7, under the hanging cup no-load condition, adjusting the dynamic rotation balance of the horizontal rotor to control the dynamic unbalance amount of the centrifuge to reach a set value; Step S8, after the heat preservation is completed, the vacuum-heated crucible is taken out from the muffle furnace and placed inside the hanging cup of the centrifuge, and then the centrifuge is started, and the speed of the horizontal rotor is adjusted so that the horizontal rotor carries the crucible to rotate; Step S9: During the rotation of the horizontal rotor, after the crucible is completely cooled to room temperature, the bulk ingot is taken out to obtain a duplex hypoeutectic copper-zirconium alloy sample.

4. The method for preparing a dual-phase hypoeutectic copper-zirconium alloy according to claim 3, characterized in that: In the step S1, the mass ratio of electrolytic copper to metal zirconium is 4:96 to 6:

94.

5. The method for preparing a dual-phase hypoeutectic copper-zirconium alloy according to claim 3, characterized in that: In the step S2, the ultrasonic cleaning agent used to ultrasonically clean the cast ingot is anhydrous ethanol.

6. The method for preparing a dual-phase hypoeutectic copper-zirconium alloy according to claim 3, characterized in that: The vacuum heating conditions of the crucible in the muffle furnace in step S5 are as follows: the vacuum degree is greater than 10-3Pa, the crucible is heated with the muffle furnace to a temperature not lower than 1250°C, and the heat preservation time is not lower than 45 minutes.

7. The method for preparing a dual-phase hypoeutectic copper-zirconium alloy according to claim 3, characterized in that: In step S7, the dynamic unbalance of the centrifuge is less than 2 g·mm.

8. The method for preparing a dual-phase hypoeutectic copper-zirconium alloy according to claim 3, characterized in that: In the step S8, the rotation speed of the horizontal rotor is adjusted so that the rotation speed of the crucible is greater than 1000 r / min.

9. The method for preparing a dual-phase hypoeutectic copper-zirconium alloy according to claim 3, characterized in that: In the step S8, a heat-insulating sleeve is filled between the vacuum-heated crucible and the inner wall of the hanging cup to reduce heat loss along the side wall of the crucible, and the thermal conductivity of the heat-insulating sleeve is lower than 0.2 W / (m·K).

10. The method for preparing a dual-phase hypoeutectic copper-zirconium alloy according to claim 3, characterized in that: The vacuum heating conditions of the crucible in the muffle furnace in step S5 are as follows: the crucible is heated to 1300° C. with the muffle furnace, and the heat preservation time is 60 minutes.

Citation Information

Patent Citations

  • Cu-zr-based copper alloy plate and process for manufacturing same

    CN103380221B

  • Copper alloy sheet with excellent electrical conductivity and stress relaxation characteristics

    CN104718302B

  • A high-strength and high-conductivity rare-earth copper-zirconium alloy and its preparation method

    CN105088010B

  • Copper alloy for electrical and electronic equipment, copper alloy thin sheet for electrical and electronic equipment, parts, terminals and busbars for electrical and electronic equipment

    CN105452502B

  • Copper-zirconium alloy for electronic component and preparation method of copper-zirconium alloy

    CN111411256A